Associations between Macular OCT Angiography and Nonproliferative Diabetic Retinopathy in Young Patients with Type 1 Diabetes Mellitus - Nina C. B. B. Veiby; Aida Simeunovic; Martin Heier; Cathrine Brunborg; Naila Saddique; Morten C. Moe; Knut Dahl-Jørgensen; Hanna D. Margeirsdottir; Goran Petrovski (Journal of Diabetes Research)
Background/Objective. Optical coherence tomography angiography (OCTA) is increasingly used to supplement ophthalmoscopy in the diagnosis and follow-up of diabetic retinopathy. Our objective was to confirm if OCTA parameters can predict the development of nonproliferative diabetic retinopathy (NPDR) and to clarify if any single OCTA parameter is associated with NPDR independently of well-known risk factors in young type 1 diabetes (T1D) patients. Methods. OCTA of both eyes was performed in a cross-sectional study of 14 to 30-year-old individuals with at least 10-year duration of T1D and controls recruited from the Norwegian Atherosclerosis and Childhood Diabetes (ACD) study. Vessel density (VD) and foveal avascular zone (FAZ) area in the superficial and deep capillary plexus (SCP and DCP), total retinal volume (TRV), and central macular thickness (CMT) were calculated using automated software. Univariate and multivariate ordered logistic regression (OLR) models were used accordingly. Results. We included 168 control eyes and 315 T1D eyes. Lower VD in DCP (OR 0.65, 95% CI 0.51–0.83), longer diabetes duration (OR 1.51, 95% CI 1.22–1.87), and higher waist circumference (OR 1.08, 95% CI 1.02–1.14) were significantly associated with progression of NPDR. VD in SCP and DCP were significantly lower in T1D patients without diabetic retinopathy than in controls. Conclusions. Sparser VD in DCP is significantly associated with severity of NPDR, supporting that OCTA might detect the earliest signs of NPDR before it is visible by ophthalmoscopy.